a) x+2(3-x)-3(1-x)=9
<=> x+6-2x-3+3x=9
<=> 2x+3=9
<=> 2x=6
<=> x=3
b) (3x+5)-(x-10)+2x=31
<=> 3x+5-x+10+2x=31
<=> 4x+15=31
<=> 4x=16
<=> x=4
a) x+2(3-x)-3(1-x)=9
x+6-2x-3+3x=9
x-2x+3x=9-6+3
2x=6
x=6:2
x=3
Vậy x=3
b) (3x+5)-(x-10)+2x=31
3x+5-x+10+2x=31
3x-x+2x=31-5-10
4x=16
x=16:4
x=4
Vậy x=4
a, x + 2(3 - x) - 3( 1 - x) = 9
<=> x + 6 - 2x - 3 + 3x = 9
<=> x - 2x + 3x = 9 - 6 +3
<=> 2x = 6
<=> x = 3
Vậy_
b, ( 3x + 5) - ( x - 10) + 2x = 31
<=> 3x + 5 - x + 10 + 2x = 31
<=> 3x - x + 2x = 31 - 5 - 10
<=> 4x =16
<=> x = 4
Vậy_